Lambl's excrescence and the safety of radiofrequency ablation for atrial fibrillation. Issue 7 (13th June 2022) - Zuo, Song; Bo, Xiaowen; He, Liu; Jiang, Chao; Dai, Tianyi; Cui, Jing; Li, Xu; Wu, Jiahui; Li, Xin; Li, Songnan; Liu, Nian; Jiang, Chenxi; et al.
Abstract: Background: Lambl's excrescences (LEs) are excrescences with an extremely low incidence, mainly ultrasound diagnosed. Increasingly, LEs are detected by transesophageal echocardiography before catheter ablation, which raises safety concerns on whether LEs were associated with an embolism event during or after ablation, but clinical data are still lacking. Methods and Results: We consecutively recruited 8081 patients with atrial fibrillation who underwent radiofrequency catheter ablation in Beijing Anzhen Hospital from Jan 1, 2017 to Dec 31, 2019. Total 21 patients (0.3%) were diagnosed as LEs with an average age of 70.8 ± 8.9 years, and 38.1% were male. Persistent atrial fibrillation (PeAF) and paroxysmal atrial fibrillation (PAF) accounted for 57.1% (12 cases) and 42.9% (nine cases), respectively. LEs were mostly frequently observed on the aortic valve (18 cases, 75%) and mitral valve (six cases, 25%). Precisely, the noncoronary cusp is ranked first in terms of the LEs presence (seven cases, 29.2%), followed by the right coronary cusp (six cases, 25.0%), the left coronary cusp (five cases, 20.8%), the anterior mitral valve (four cases, 16.7%), and the posterior mitral valve (two cases, 8.3%). During the ablation for LEs patients, the average procedure time was 96.0 ± 22.4 min; the average fluoroscopy time was 4.2 ± 0.8 min; the average total ablation time was 20.6 ± 5.6 min; and the mean hospital stay was 3.3 ± 0.6 days. No patients suffered from serious complications during the procedure. Furthermore, no cardiovascular event was observed during a follow‐up of 19.1 ± 11.8 months. Conclusions: There was no clear association between LEs with intraoperative embolism events or cardiovascular events during the follow‐up period.